(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to identify the role of endowments (Waqf) in the sustainability of family businesses, focusing on family firms with endowments in the Kingdom of Saudi Arabia to explore their challenges, examine the role of endowments in ensuring corporate continuity, and investigate their impact on achieving generational succession. To achieve these objectives, the study adopted a descriptive survey methodology utilizing a mixed-methods approach, implementing a questionnaire for the quantitative component and semi-structured interviews for the qualitative component. The study population consisted of all officials in Saudi family businesses with endowments whose roles pertain to family operations and the endowment, from which a convenience sample of 51 officials completed a physically distributed questionnaire, while semi-structured interviews were conducted—both face-to-face and via Zoom—with 8 family endowment experts in Saudi Arabia. The findings revealed that endowments actively contribute to the sustainability of 48% of family businesses up to the second generation, maintain the survival of 21% up to the third generation, and ensure the continuity of 6% into the fourth generation. Furthermore, the results indicated that the endowment serves as a genuine safeguard for preserving inheritance, growing wealth, and avoiding liquidation cycles that often terminate the legacy of major companies upon the founder’s absence. However, the study highlighted that the most prominent challenges facing these businesses include a shortage of qualified personnel to manage endowments, a lack of clarity regarding their strategic vision, weak financial planning, difficulties in aligning company interests with the conditions set by the endowers (Waqifis), and the presence of family disputes that negatively impact endowment utilization. Ultimately, the results demonstrated that endowments play a significant role in generational succession planning, preserving family unity and cohesion, and reducing conflicts among family members; consequently, the study recommends that family businesses actively establish endowments to safeguard both family and wealth, train rising generations, and formulate a mutually agreed-upon generational succession plan.